High nonvolatile modulation of resistance on a ferroelectric PbZr0·2Ti0·8O3 /Nd0.3Sm0.25Sr0·45MnO3 liquid-gated electric-double-layer transistors. (March 2020) - Shao, F.; Zhang, L.P.; Zhang, F.Q.; Teng, J.; Chen, J.K.; Xu, X.G.; Miao, J.; Jiang, Y.
Abstracts: A ferroelectric polarization field electric-double-layer transistor based on the PbZr0·2 Ti0·8 O3 (PZT)/Nd0.3 Sm0.25 Sr0·45 MnO3 (NSSMO) structure gated by ionic-liquid was established. The electrostatic modulation on the NSSMO channel was performed by applying electric field, while the respective non-volatile field effect upon the polarization field of PZT was investigated. Interestingly, a nonvolatile modulation on the resistance of NSSMO channel was observed, depending on the ferroelectric polarization field from PZT layer. Moreover, a large modulation of electrical conductivity of the NSSMO channel was achieved when applying a bias voltage of +3 V. This result indicates that a high nonvolatile electrostatic effect can be achieved in complex oxides devices under ferroelectric polarization field. Highlights: Ferroelectric PbZr0.2 Ti0.8 O3 (PZT)/ Nd0.3 Sm0.25 Sr0.45 MnO3 (NSSMO) gated by ionic-liquid was established. A nonvolatile modulation of 430 % for resistance of NSSMO channel can be induced by PZT ferroelectric field. High modulation of conductivity in the NSSMO channel 13900 % was achieved by VG +3 V. Such nonvolatile modulation of PZT/NSSMO ferroelectric-EDLT shows a potential in the nonvolatile memory application.